2014
DOI: 10.1097/cmr.0000000000000065
|View full text |Cite
|
Sign up to set email alerts
|

Melanoma risk is associated with vitamin D receptor gene polymorphisms

Abstract: Previous studies have reported that vitamin D receptor (VDR) gene polymorphisms are associated with the occurrence of various cancers, including melanoma. The aim of the current study was to investigate the association of VDR gene polymorphisms with melanoma risk, clinicopathological characteristics, and vitamin D levels. The study group included 117 patients (84 patients with superficial spreading melanoma and 33 patients with nodular melanoma). The control group included 122 sex-matched and age-matched healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
21
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 29 publications
4
21
0
2
Order By: Relevance
“…2-13.3) genes code for key enzymes involved in vitamin D anabolism and catabolism, 25-hydroxyvitamin D-1-hydroxylase and 25-hydroxyvitamin D-24-hydroxylase, respectively [11]. Identified polymorphisms in vitamin D related genes were extensively studied in relation to various types of diseases, such as cancer [14][15][16], autoimmune [17,18], and inflammatory diseases [19,20]. Our research group previously reported association between VDR and CYP24A1 gene polymorphisms with oral cancer risk and survival [21], while polymorphisms in these genes have not previously been investigated in OLP patients.…”
Section: Introductionmentioning
confidence: 99%
“…2-13.3) genes code for key enzymes involved in vitamin D anabolism and catabolism, 25-hydroxyvitamin D-1-hydroxylase and 25-hydroxyvitamin D-24-hydroxylase, respectively [11]. Identified polymorphisms in vitamin D related genes were extensively studied in relation to various types of diseases, such as cancer [14][15][16], autoimmune [17,18], and inflammatory diseases [19,20]. Our research group previously reported association between VDR and CYP24A1 gene polymorphisms with oral cancer risk and survival [21], while polymorphisms in these genes have not previously been investigated in OLP patients.…”
Section: Introductionmentioning
confidence: 99%
“…We identified 10 suitable studies with a total of 4,961 melanoma patients and 4,605 controls which have described associations between common VDR variants and melanoma risk (Table 1) [15-24]. The variants Apa1, Bsm1, Cdx2, EcoRV, Fok1, and Taq1 were each evaluated in at least three studies and were included in the current meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Of them, three were performed in the USA, three in UK, one in Spain, one in Italy, one in Poland, and one in Serbia. None of the included studies was derived from the HWE for genotype distribution in the controls, except for one study that was performed by the Zeljic et al [24], in which a significant difference in the frequency of Apa1 in control subjects was identified ( p  = .001). The study performed by Randerson-Moor et al [22].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations